Loop Structures Optimization and Reordering for Efficient Parallel Processing - Vancea, Alexandru; Ciaca, Monica; Avornicului, Mihai (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The problem of choosing an optimal sequence of transformations, leading to the most efficient parallel version of a program remains an open question. Related to this, compilers of the moment only manage to incorporate a set of heuristic decisions. This article treats the transformation of the program, addressing and analyzing the range of transformations of loop structures, that we consider most appropriate today. We tried to exemplify these transformations in case of groups of companies.Â